Structural evolution of the Laibid pop-up structure, Sanandaj-Sirjan Zone, West Iran - Aflaki, M.; Mohajjel, M. (TRABAJOS DE GEOLOGÍA, 2009)
The Laibid pop-up structure is located in the highly deformed sub-zone of the Sanandaj-Sirjan Zone, western Iran. In this zone, structural trends are parallel to the Zagros fold-thrust belt (NW-SE), but the pop-up structure has a different trend of E-W and is surrounded by several fault sets, which are the youngest deformational event. Comparison between the fold axes and axial plains of the inner and outer part of the pop-up structure and also coaxial interference patterns of polyfolding show a continuous deformation in the study area. It seems that during Late Jurassic, due to right lateral transpression movement resulting from the collision of the Iranian and the Afro-Arabian continents, three folding stages formed and passively rotated in a continuous deformation condition.